The Effect of Varying Tension of a Suture Button Construct in Fixation of the Tibiofibular Syndesmosis—Evaluation Using Stress Computed Tomography. Issue 2 (February 2017) - Morellato, John; Louati, Hakim; Bodrogi, Andrew; Stewart, Andrew; Papp, Steven; Liew, Allan; Gofton, Wade
Abstract : Background/Purpose: There have been no studies assessing the optimal biomechanical tension of suture button constructs. The purpose of this study was to assess optimal tensioning of suture button fixation and its ability to maintain reduction under loaded conditions using a stress computed tomography (CT) model. Methods: Ten cadaveric lower limbs disarticulated at the knee were used. The limbs were placed in a modified ankle load frame that allowed for the application of sustained torsional axial or combined torsional/axial loads. The syndesmosis and the deep deltoid ligaments complex were sectioned and the limbs were randomized to receive a suture button construct tightened at 4, 8, or 12 kg. The specimens were loaded under the 3 loading scenarios with CT scans performed after each and at the conclusion of testing. Multiple measurements of translation and rotation were compared with baseline CT scan taken before sectioning. Results: Significant lateral (maximum 5.26 mm) and posterior translation (maximum 6.42 mm) and external rotation (maximum 11.71 degrees) was noted with the 4 kg repair. Significant translation was also seen with both the 8 and the 12 kg repairs; however, the incidence was less than with the 4 kg repair. Significant overcompression (ML = 1.69 mm, B = 2.69 mm) was noted with the 12 kg repair and also with the 8 kg repair (B = 2.01 mm). Conclusion: Suture button constructs must be appropriately tensioned to maintain reduction and re-approximate the degree of physiological motion at the distal tibiofibular joint. These constructs also demonstrate overcompression of the syndesmosis; however, the clinical effect of this remains to be determined.